Plasminogen modulates formation and release of platelet angiogenic regulators - A. A. Tykhomyrov; D. D. Zhernosekov; T. V. Grinenko (The Ukrainian Biochemical Journal, 2020)
Platelets store, produce and release a variety of angiogenesis regulators, which can contribute to both normal tissue repair and angiopathy-associated pathologies. Plasminogen has been earlier shown to regulate some platelet functions, but if it is able to modulate angiogenic capacities of platelets is still poorly studied. Thus, the aim of the present study was to evaluate the effects of different plasminogen forms on the formation and secretion of angiogenic protein regulators by platelets. Human washed platelets were obtained by gel-filtration on Sepharose-2B. The levels of P-selectin (CD-62P) exposed on the plasma membrane of untreated and activated platelets was monitored by flow cytometry. Secretion of platelet-derived vascular endothelial growth factor (VEGF) as well as plasminogen fragmentation and angiostatin formation by intact platelets and platelet plasma membranes were analyzed by immunoblotting. It was shown that thrombin or collagen exposure resulted in enhanced P-selectin surface expression by platelets, while Lys-form of plasminogen reduced agonist-induced platelet secretion. Lys-plasminogen, but not Glu-form, inhibited agonist-induced VEGF release from platelets. Activation of platelets significantly accelerated plasminogen cleavage and angiostatin formation. Anti-actin antibodies inhibited plasminogen fragmentation during incubation with platelet plasma membranes indicating surface-exposed actin participation in plasminogen conversion to angiostatins. The present study uncovers a novel function of plasminogen to limit angiogenic potential of platelets via angiostatin formation and inhibition of VEGF secretion.